Decellularization and Solubilization of Porcine Liver for Use as a Substrate for Porcine Hepatocyte Culture - Ramon E. Coronado; Maria Somaraki-Cormier; Shanmugasundaram Natesan; Robert J. Christy; Joo L. Ong; Glenn A. Halff (Cell Transplantation, 2017)
Biologic substrates, prepared by decellularizing and solubilizing tissues, have been of great interest in the tissue engineering field because of the preservation of complex biochemical constituents found in the native extracellular matrix (ECM). The integrity of the ECM is critical for cell behavior, adhesion, migration, differentiation, and proliferation that in turn affect homeostasis and tissue regeneration. Previous studies have shown that various processing methods have a distinctive way of affecting the composition of the decellularized ECM. In this study, we developed a bioactive substrate for hepatocytes in vitro, made of decellularized and solubilized liver tissue. The present work is a comparative approach of 2 different methods. First, we decellularized porcine liver tissue with ammonium hydroxide versus a sodium deoxycholate method, then characterized the decellularized tissue using various methods including double stranded DNA (dsDNA) content, DNA size, immunogenicity, and mass spectrometry. Second, we solubilized the decellularized porcine liver with hydrochloric acid versus acetic acid (AA) and characterized the resultant solubilized tissues using relevant methodologies including protein yield, immunogenicity, and bioactivity. Finally, we isolated primary porcine hepatocytes, cultured, and evaluated their bioactivity on the optimized decellularized–solubilized liver substrate. The decellularized porcine liver ECM processed by the ammonium hydroxide method and solubilized with AA displayed higher ECM integrity, low dsDNA, no evidence of intact nuclei, low human monocyte chemoattraction, and the presence of key molecules typically found in the native liver, a very important element for normal cell function. In addition, primary porcine hepatocytes showed enhanced functionality including albumin and urea production and bile canaliculi formation when cultured on the developed liver substrate compared to type I collagen.